The Dilemma of Food Sovereignty and Supply Gaps: A Socio-Economic Analysis of the Free Nutritious Meals Program and Its Impact on the Resilience of Local Farmers: Dilema Kedaulatan Pangan dan Kesenjangan Pasokan: Analisis Sosio-Ekonomi Program Makan Bergizi Gratis terhadap Ketahanan Peternak Lokal - Arif Rahman Azis; Woki Bilyaro; Muhammad Dani; Nurazizah Ramadhanti; Rizky Amrullah Chaniago; Akbar Abdurrahman Mahfudz; Muhammad Subhan Hamka; Muhammad Hakim (Buletin Peternakan Tropis, 2026)
The Free Nutritious Meal Program (MBG), positioned as a "Big Push Strategy" to eradicate stunting and accelerate human capital development towards the Golden Indonesia 2045 vision, introduces an unprecedented demand shock to the national macroeconomic architecture. With a target of 82.9 million beneficiaries and an initial fiscal commitment of Rp71 trillion, the policy mandates the daily provision of massive animal protein, thereby exposing severe structural vulnerabilities within the domestic livestock supply chain. This study evaluates the socio-economic impact of the MBG program on the resilience of local farmers, transitioning the analytical lens from conventional clinical health outcomes to rural agrarian economics. Utilizing an Explanatory Sequential Design, the research integrates macro-statistical time-series data of livestock production and the Farmer's Terms of Trade for the Livestock subsector (NTP-T) with institutional political economy analysis. The findings reveal a critical supply-demand gap, notably an 8.5 million-ton deficit in fresh milk and a structural reliance on beef imports, which forces a policy dilemma between pragmatic mass importation and the philosophical pursuit of food sovereignty. While excessive imports risk marginalizing smallholder farmers and distorting farm-gate prices, decentralized local procurement demonstrates a profound multiplier effect. The NTP-T index recorded a consistent appreciation, peaking at 125.35 points in December 2025, validating that localized fiscal injections via nutrition service units significantly enhance farmers' purchasing power. To mitigate the structural asymmetry of smallholder farming and prevent corporate hegemony, the study concludes that the revitalization of Village Unit Cooperatives (KUD) and the implementation of the People's Animal Husbandry School (SPR) model are imperative. Policy recommendations emphasize mandatory local sourcing quotas, menu flexibility, and targeted capital expenditures for cold chain infrastructure.